An Assessment of the Effectiveness of Performance Appraisal System in Educational Institution: IAMTECH Sierra Leone as a case study (International Journal of Scientific Research and Management (IJSRM), 2018)
Human Resource Management (HRM) plays vital role in an educational institutions. HRM is an essential ingredient for changing the scope and dynamism of for evaluating worker’s performance. Performance appraisal permits institution to supervise their employee’s performance relating to competencies, punctuality, pedigree and potentials. Ignoring effective performance appraisal system results to low performance of staff work output. Institutional objectives can be achieve by effectively applying performance appraisal system with diverse positive outcomes diligently monitoring both academic and administrative staff of the Institute of Advanced Management and Technology (IAMTECH) Sierra Leone. Effective performance management and appraisal system has ultimately improved staff performance and influences their potentials in thinking, and doing work. Importantly, it brings benefits to employer and employee by creating a plain level ground for both parties. Furthermore, performance appraisal system delivers a complete assessment of staff performance at IAMTECH with a comprehensive purposes, benefits, and challenges of performance appraisal system. However the researcher establishes dissatisfaction with some appraisal processes, such as management not backing the appraisal process, authorities are not questioned for not completing their appraisal process on time, and the absence of performance appraisal workshop/seminar/training provided to authorities and staff at IAMTECH and more importantly, the performance appraisal system is done yearly at IAMTECH. IAMTECH uses rating scale, descriptive system and management by objective system methods of appraisal to evaluate employees. Noting that management by objective is the mostly used method and hence, our method of effective performance appraisal system has created positive influence on job performance at IAMTECH staff and management.